QUANTITATIVE PET/CT FOR MYOCARDIAL VIABILITY ASSESSMENT AFTER COMPLEX PCI: EXPLORING THE ROLE OF MICROBIAL INFECTIONS AND INFLAMMATORY BIOMARKERS - Dr Hazrat Ullah Khan; Dr Muhammad Umer Khan Khalil; Dr Rashid Iqbal; Dr Zubeda Irshad; Dr Rakhshanda Naheed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
To assess myocardial viability using quantitative PET/CT in patients following complex PCI and explore the role of microbial infections and inflammatory biomarkers in predicting myocardial recovery. Methods: This prospective study included 71 patients who underwent complex PCI at Ayub Teaching Hospital, Abbottabad, between January 2023 and January 2024. PET/CT using 18F-FDG was performed post-PCI to evaluate myocardial viability. Blood samples were collected to analyze inflammatory biomarkers including CRP and IL-6. Microbial infection status was also assessed. Follow-up echocardiography was used to evaluate myocardial recovery. Results: The majority of patients demonstrated viable myocardium on PET/CT imaging, with 60% of the cohort showing functional myocardial improvement on follow-up. Inflammatory biomarkers, including CRP and IL-6, were moderately elevated in several patients; however, statistical analysis revealed no significant association between these markers and myocardial recovery (p > 0.05). Infection was identified in nearly one-third of the patients. Among those with positive findings, Chlamydia pneumoniae was the most frequently detected organism (n = 15), followed by Helicobacter pylori (n = 11) and Cytomegalovirus (n = 4). Despite the presence of these pathogens, no statistically significant correlation was found between infection status or specific microbial species and myocardial recovery outcomes. The majority of patients (n = 41) had no detectable infection. These findings suggest that neither systemic inflammation nor underlying chronic infections had a measurable impact on post-PCI myocardial functional improvement in this study population. Conclusion: Quantitative PET/CT proved to be a reliable imaging tool for assessing myocardial viability following complex PCI. Although inflammatory markers and microbial infections were prevalent among patients, their presence did not significantly influence myocardial recovery. This underscores the importance of direct metabolic myocardial assessment through PET/CT over reliance on systemic biomarkers or infection status when evaluating viability and guiding post-revascularization care.